Legislazione linguistica e percezione dell’alterità: intorno al fallimento della tutela delle minoranze linguistiche storiche in Italia - Toso, Fiorenzo (Verbum – Analecta Neolatina, 2007)
This paper illustrates the problems that arose after the approval of a law in Italy (Act no. 482/1999) on the safeguarding and enhancement of traditional linguistic minorities by examining a number of specific examples. The law proved to be not only seriously insufficient, but even had negative repercussions, both with regard to the overall judgement expressed on Italy’s linguistic heritage seen as a cultural heritage, and with regard to the fact that in many situations the very principal of protection was distorted: from the refusal to finance a number of groups rightfully and meritoriously entitled to such funds to the financing of local realities which have very little if nothing to do with linguistic varieties. In general, "language policy" in Italy is negatively influenced by the confusion between "national minority" and "linguistic minority", one of the major factors in accounting for the failure of initiatives attempting to help the linguistic minorities.